The Effectiveness of Social Media Utilization in Marketing Success of e-Pharmacies in Saudi Arabia - Ghadeer, Mohammed Al; Falah, Khaled Al; Afaneh, Jehad Abdallah; Moustafa, Mohamed A; Albarq, Abbas N; Elrayah, Musaddag; Suleiman, Amal k (Journal of Posthumanism, 2025)
This study examines the effectiveness of social media utilization in the marketing success of e-pharmacies in Saudi Arabia, focusing on disease awareness campaigns, product promotion, social media marketing, and corporate social responsibility (CSR). Using a quantitative research design, data were collected from 240 licensed pharmacists and social media users in Saudi Arabia through a structured survey. SPSS software was used for descriptive statistics, multiple regression analysis, and reliability testing. The findings indicate that social media marketing (B=0.422, p<0.001) had the strongest impact on e-pharmacy success, followed by disease awareness campaigns (B=0.274, p<0.001) and product promotion (B=0.168, p=0.007). However, CSR (B=0.081, p=0.083) did not show a statistically significant impact. The model explained 77% of the variance (R²=0.77) in e-pharmacy marketing success. The study highlights the growing role of social media in enhancing brand visibility, consumer trust, and engagement. Findings suggest that optimizing digital marketing strategies, increasing disease awareness, and leveraging targeted product promotion can significantly improve e-pharmacy adoption and consumer satisfaction. This research contributes to the academic discourse on digital marketing in healthcare and provides actionable insights for pharmaceutical companies, policymakers, and marketers seeking to enhance online engagement and consumer confidence in the Saudi e-pharmacy sector.